2013
DOI: 10.1109/tcsi.2012.2209295
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Oscillations in Resonant Electrostatic Vibration Energy Harvesters

Abstract: International audienceIn this paper, we present a formal analysis and description of the steady-state behavior of an electrostatic vibration energy harvester operating in constant-charge mode and using different types of electromechanical transducers. The method predicts parameter values required to start oscillations, allows a study of the dynamics of the transient process, and provides a rigorous description of the system, necessary for further investigation of the related nonlinear phenomena and for the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…As a matter of fact, it's an attempt to synthesize two efficient methods to get a much more efficient one.Elena blokhina et al offered a formal analysis and description of the steady-state behaviour of an electrostatic vibration energy harvester operating in constant charge mode and used different types of electromechanical transducers [2]. The majority of the electrostatic converters' shapes are derived from accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, it's an attempt to synthesize two efficient methods to get a much more efficient one.Elena blokhina et al offered a formal analysis and description of the steady-state behaviour of an electrostatic vibration energy harvester operating in constant charge mode and used different types of electromechanical transducers [2]. The majority of the electrostatic converters' shapes are derived from accelerometers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [10][11][12] presented extended dynamical analysis of a very common configuration of resonant e-VEHs based on a gap-closing transducer operating in constant-charge mode [1]. Reference [11] proposed a straightforward analytical description of the regular and desirable behaviour of the system whose characteristics (the amplitude of oscillations, the converted power, etc.) are calculated from parameters of the system (a resonator coupled with a conditioning circuit) and from the environmental parameters (the magnitude and frequency of external vibrations).…”
mentioning
confidence: 99%
“…The study presented in this paper uses the results of [10][11][12] to predict the maximum power that can be converted by an e-VEH with the common gap-closing transducer. It was found that e-VEHs utilising the gap-closing transducer and operating in the constant-charge triangular QV (charge-voltage) cycle [1] have a constant universal factor Π max relating the maximum convertible power to the product of the basic system parameters.…”
mentioning
confidence: 99%
See 2 more Smart Citations